Analysis of Energy Balance in Obese Healthcare Workers - Nani Cahyani Sudarsono; Ria Lestari; Tiffany Georgine T'sidkenu Widjaja (Faculty of Public Health Universitas Indonesia, 2023)
Obesity is a global health challenge that seriously affects developing countries, including Indonesia. Although the determining factors of obesity are complex, energy balance and lifestyle play a very important role. Unbalanced dietary patterns and sedentary behavior are still the most important factors in the occurrence of obesity. Therefore, it is important to discover the energy balance calculated from energy intake and energy expenditure in obese patients. This study aimed to analyze the balance of energy intake and expenditure, body composition, and physical activity level in obese patients at Exercise Center IMERI FKUI. A cross-sectional study was held at Exercise Center IMERI FKUI. Study participants (patients) were screened by measuring body composition and obesity status was determined based on BMI data (≥25 kg/m2). The selected subjects were then administered to data collection on body composition using the MF-BIA instrument, energy intake using the MyFitnessPal (MFP) application, as well as energy expenditure and physical activity level using the IPAQ-SF tool. From a total of 12 patients with obesity at the Exercise Center, 11 (91.67%) patients had a negative energy balance and 1 (8.33%) patient had a positive energy balance during a 7-day period of data collection. A majority of the obese patients at the Exercise Center reported a negative energy balance.